PENGARUH EKUITAS MEREK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK IPHONE - Muhammad Nur Pajar Nofan; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
This study aims to determine the effect of brand equity and product innovation on consumer purchasing decisions on iphone products (a case study on the millennial generation in Bengkulu City). This type of research is a quantitative descriptive research, the object of this research is the millennial generation in Bengkulu City. The sampling method used a non-probabilty technique, namely accidental sampling. The number of respondents in this study were 150 people. Methods of data collection using a questionnaire. The data analysis technique uses Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely t-test and f-test. The results of this study can be concluded that the Brand Equity variable has a positive effect on Consumer Purchase Decisions, Product Innovation has a positive effect on Consumer Purchase Decisions, and Brand Equity and Product Innovation together have a positive and significant effect on Consumer Purchase Decisions. Keywords: Brand Equity, Product Innovation and Consumer Purchase Decision